Efektivitas Program Sekolah Penggerak di UPTD SMPN 4 Poco Ranaka Desa Watu Lanur Kecamatan Lamba Leda Selatan Kabupaten Manggarai Timur Nusa Tenggara Timur - Siti Sobariyah; Khaerul Umam Noer (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The effectiveness of the driving school program at UPTD SMPN 4 Poco Ranaka. The purpose of this study was to analyze the effectiveness of the driving school program at UPTD SMPN 4 Poco Ranaka. The method used is descriptive qualitative with data collection through interviews, observation and documentation using the theory of Sutrisno (2010), this study uses five indicators of Program Understanding, Target Accuracy, Timeliness, Achievement of Goals, Real Change. The results show that the effectiveness of the driving school program at UPTD SMPN 4 Poco Ranaka, Program Understanding where the programs have been implemented in accordance with regulations, Target Accuracy where the accuracy of the target in P5 activities is almost effective in implementing its activities, it's just that it is still hampered by facilities and infrastructure, Timeliness of local wisdom activities, entrepreneurship, The achievement of goals where the activities of teachers have run in accordance with the regulations of these activities, it's just that they are still constrained by the lack of regional participation, Real Change with the school program driving teachers, students and the community to get a positive impact from the program so that school residents can explore well in their activities. From the activities and programs that have been carried out, it has reached 85%, it is almost effective with the driving school program at UPTD SMPN 4 Poco Ranaka.